FAKTOR PEMBENTUK MOTIVASI BELAJAR MAHASISWA DAN PERBEDAANNYA BERDASARKAN GENDER - Nengah Sukendri (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
This study aims to analyze form factor motivation to learn students and the difference by gender in STAHN Gde Pudja Mataram. Kind of research that is used is comparative with quantitative analysis tools of confirmatory factor to find factors that form the motivation to learn a student and t-independent tests to know the difference by gender. student motivationThe research results show that the factors that form the motivation of students for college in stahn gde pudja mataram is motivation intrinsic and extrinsic motivation, and as a whole there has been gender equality for men and women especially in terms point of view both intrinsic and extrinsic Motivation.